2011
DOI: 10.1111/j.1525-142x.2011.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

AGAMOUS subfamily MADS-box genes and the evolution of seed cone morphology in Cupressaceae and Taxodiaceae

Abstract: In this comparative developmental genetics study, we test hypotheses based on fossil and morphological data on reproductive organ morphology and evolution in conifers--specifically, the ovule-bearing organ in Cupressaceae and Taxodiaceae. Genes homologous to the Arabidopsis gene AGAMOUS are expressed in ovuliferous scales of spruces (Picea) throughout development. Previous studies have shown that the AGAMOUS subfamily of MADS-box genes predates the split between angiosperms and gymnosperms, and that these gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…We suggest that this result might be due to random higher similarities between GGM3, PodAG , and TgAG in the small matrix we analyzed. This suggestion is supported by the results presented in the accompanying paper by Groth et al (2011), where the matrix analyzed phylogenetically included a much larger sampling of AG ‐related sequences from gymnosperms as well as angiosperms. In their cladogram, Groth et al (2011) have found that GGM3 is sister branch of a clade composed exclusively by conifer sequences, as expected from the aforementioned molecular systematics works.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…We suggest that this result might be due to random higher similarities between GGM3, PodAG , and TgAG in the small matrix we analyzed. This suggestion is supported by the results presented in the accompanying paper by Groth et al (2011), where the matrix analyzed phylogenetically included a much larger sampling of AG ‐related sequences from gymnosperms as well as angiosperms. In their cladogram, Groth et al (2011) have found that GGM3 is sister branch of a clade composed exclusively by conifer sequences, as expected from the aforementioned molecular systematics works.…”
Section: Discussionsupporting
confidence: 61%
“…2), it can be observed that both PodAG and TgAG, and the four cycad genes CerAG, MacAG, StaAG, and ZamAG, contain recognizable versions of the AG Motifs I and II identified by Kramer et al (2004). A complementary cladistic analysis on a matrix of translated sequences including several additional AG-subfamily homologs from gymnospermsFincluding three new putative orthologs from Cupressaceae/Tax-odiaceaeFand angiosperms is presented in the accompanying paper by Groth et al (2011).…”
Section: Identification Of Six Novel Gymnosperm Ag-subfamily Homologsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcription factors of the MADS-domain family play key roles in both processes, in addition to LEAFY (LFY), which acts as an initiator of the floral-organ identity MADS-box genes. The gymnosperm homologues to the MADS-box C-class genes, in angiosperms specifying carpel identity and, together with the B genes, stamen development, are all expressed in ovule-carrying and pollen-producing organs, whereas B-class homologues appear to be specific to the pollen-producing organs (Tandre et al, 1995(Tandre et al, , 1998Rutledge et al, 1998;Sundstr€ om et al, 1999;Winter et al, 1999;Sundstr€ om & Engstr€ om, 2002;Carlsbecker et al, 2003Carlsbecker et al, , 2004Jager et al, 2003;Zhang et al, 2004;V azquez-Lobo et al, 2007;Englund et al, 2011;Groth et al, 2011;Lovisetto et al, 2012). Hence, a substantial conservation of reproductive development control is apparent and implies that C-class homologues specify reproductive identity and B-class homologues distinguish male from female identity in all seed plant groups.…”
Section: Introductionmentioning
confidence: 99%
“…More surprisingly, despite markedly petaloid shape, the late expression of C- function gene was detected in the corona of daffodil [19], which suggested that corona might have a stamen-like origin but with changes of developmental pathways that dictating morphogenesis [19]. AGAMOUS ( AG ) is the only C class gene in Arabidopsis and its function in many higher plants including monocots are highly conserved [20,21]. In Davidia involucrata , the bract organ resembled petals, yet expressions of both B- and C- function homologs were detected [22], suggesting that certain expression combinations of ABC genes may not be sufficient to specify expected floral organ identities.…”
Section: Introductionmentioning
confidence: 99%